ANALISIS PENJUALAN KREDIT PADA DEPARTEMENT SPARE PART PT. MAHAKAM BERLIAN SAMJAYA SAMARINDA - sari, Ranti Ratna (EKONOMIA, 2014)
Credit Sales Analysis By Parts Department PT.Mahakam Berlian SamjayaÂ  are one Show Room / Dealer selling Mitsubishi units are managed well developed ranging from car sales, service Flashlight, and complete Spare Parts sales. The purpose of the study was to find out how much corporate profits at the expense incurred. In addition, as a company's information and material consideration in decision making.The issues raised in this paper is the one which is most benefit / profit of company policy with the payment terms 10/15 net 30 5/30 n/45 2/45 n/60. While the hypothesis is formulated that is anticipated credit sales with 10/15 net 30 ie credit sales with a 10% discount if paid within 15 days if the expiration of 15 days then do not get a discount. Â Policy on condition 5/30 n/45 ie credit sales with a 5% discount if paid within 30 days if the passing of 30 30-day limit does not get a discount, 2/45 n/60 ie credit sales with a 2% discount if paid within 45 days and if the expiration of 45 days then it will not get a discount with the policy can provide benefits / profits in the company. Based on sales data in 2009, 2010 and 2011 profits derived from credit sales Parts Department PT. Mahakam Berlian Samarinda is: that credit sales without discounts more profitable than credit sales with discounts for Parts Department PT. Mahakam Berlian Samarinda.Terms of policy lending policy of the company is given with the payment terms of 30 days without discount (net 30) provide the most benefit / profit for the company can be seen from the increased sales pertahunya. Thus the more good a service company to the consumer it will affect the sales turnover of the company so that profits / income of the company is increasing.